2019
DOI: 10.1126/sciimmunol.aau8125
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-dependent islet autoimmunity with systemic antibody responses to intestinal commensal bacteria in children

Abstract: Microbiome sequence analyses have suggested that changes in gut bacterial composition are associated with autoimmune disease in humans and animal models. However, little is known of the mechanisms through which the gut microbiota influences autoimmune responses to distant tissues. Here, we evaluated systemic antibody responses against cultured human gut bacterial strains to determine whether observed patterns of anticommensal antibody (ACAb) responses are associated with type 1 diabetes (T1D) in two cohorts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…It was reported that secretory IgA has the capacity to bind bacteria and regulate the composition and function of gut microbiota (23). More recently, differences in IgA binding to bacteria have been linked to both inflammatory bowel disease and T1D (24,25). Thus, we investigated the proportion of IgA-bound bacteria in our study subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that secretory IgA has the capacity to bind bacteria and regulate the composition and function of gut microbiota (23). More recently, differences in IgA binding to bacteria have been linked to both inflammatory bowel disease and T1D (24,25). Thus, we investigated the proportion of IgA-bound bacteria in our study subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, bacteria bound by IgA are more colitogenic than non-IgA-bound bacteria in inducing colitis (24). To this end, a recent study showed that serum IgA from individuals with T1D has a differential ability to bind specific bacteria compared with that from healthy controls (25). Furthermore, IL-10 production from recirculating intestinal IgA + B cells protected mice from developing autoimmune encephalomyelitis (26).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show for the first time that the protective HLA class II haplotypes DRB1*15:01-DQB1*06:02 and DRB1*07:01-DQB1*03:03 are less prevalent amongst individuals diagnosed at <7 years compared with controls and those diagnosed at ≥13 years. Therefore, the earliest and most aggressive phenotypic subtype of T1D results primarily from carriage of high risk alleles and haplotypes of the HLA class II and I genes, which probably act at four levels: (i) altering the T cell receptor repertoire in favour of anti-islet antigen reactivity, for example preproinsulin, and/or reducing the protective repertoire of T regulatory cells; (ii) providing a strong autoantigen presentation environment in the islets and pancreatic draining lymph nodes enabling the infiltration and cytolytic activity of CD8 + T cells but also by disrupting B cell anergy 13 permitting binding and presentation of autoantigen to provide potent help to T cells in a self-reinforcing spiral of autoreactivity; (iii) affecting the immune response to the viral infections that are involved in the disease; (iv) affecting how the gut microbiome develops in early life, a system that is known to affect T1D susceptibility 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Her team has built a platform to identify antibacterial antibodies in blood. Analysing samples from children at high risk of type 1 diabetes, the platform revealed important clues about who would develop the disease 6 .…”
Section: Microbes In the Clinicmentioning
confidence: 99%